Influence of Different Heat Treatments on Torsional and Cyclic Fatigue Resistance of Nickel–Titanium Rotary Files: A Comparative Study - Gianluca Gambarini; Andrea Cicconetti; Dario Di Nardo; Gabriele Miccoli; Alessio Zanza; Luca Testarelli; Marco Seracchiani (Applied Sciences, 2020)
Protaper Universal (PTU), Protaper Gold (PTG) (Maillefer, Ballaigues, CH), EdgeTaper (ET), and EdgeTaper Platinum (ETP) (Albuquerque, NM, USA) were tested for both torsional and flexural resistance. The aim of the present study was to evaluate the influence of proprietary heat treatment on the metallurgical properties of the aforementioned instruments. Four groups of 30 different instruments (size 20.07) were tested, then divided into two subgroups of 15 instruments—one for the cyclic fatigue test in a curved canal (90°—2 mm radius) at 300 rpm and 2.5 Ncm. The time to fracture (TtF) and fragment length (FL) were recorded. The other subgroup was subjected to the torsional test (300 rpm, 5.5 Ncm). The torque to fracture and TtF were recorded. All the instruments underwent a SEM analysis. The heat-treated instruments showed a significantly higher fatigue resistance than the non-heat-treated instruments (p < 0.05). No significant differences were found in the torsional resistance between the ET and PTU, and the ETP and PTG. However, when comparing all the groups, the heat-treated instruments showed less torsional resistance. The improvement from heat treatment was mainly found in the cyclic fatigue resistance.